The Effect Of Reward And Job Satisfaction On Employee Performance At Arteria Daya Mulia - Hilmi Fajriansyah; Siti Maryam (CV. AFDIFAL MAJU BERKAH, 2026)
Suboptimal labor productivity is a sign of issues with employee performance that can be impacted by a number of things, such as rewards and job satisfaction implemented by the company. Using a quantitative associative design, this research seeks to analyze how rewards and job satisfaction affect employee performance at PT Arteria Daya Mulia. The study involved 110 respondents selected through purposive sampling, with data collected using a five-point Likert scale questionnaire and analyzed using multiple linear regression, t-tests, and F-tests. The regression equation for this relationship is Y = -3.162 + 0.572X₁ + 0.628X₂. The results showed that Reward significantly affected Employee Performance (t = 9.310) and Job Satisfaction also had a significant effect (t = 13.261). Simultaneously, Reward and Job Satisfaction significantly influenced Employee Performance (F = 143.086) and explained 72.3% of the variance in employee performance. These findings suggest that effective reward management and high job satisfaction contribute significantly to improving employee performance.